The Russian revolution and the war : an open letter to Monsieur Shingarev, Russian minister of agriculture, member of te Provisional Government - Sarolea, Charles (Edinburgh : Everyman, 1917)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Wereldoorlog 1; revoluties; Rusland